2021
DOI: 10.1177/10497323211058164
|View full text |Cite
|
Sign up to set email alerts
|

How do Positive Deviants Overcome Health-Related Stigma? An Exploration of Development of Positive Deviance Among People With Stigmatized Health Conditions in Indonesia

Abstract: A constructivist grounded theory approach was used to understand how some people living with stigmatized health conditions develop positive deviance to overcome stigma. We examined interviews from 13 identified positive deviants living with four different stigmatized health conditions (HIV, leprosy, schizophrenia, and diabetes) in Indonesia. Positive deviance develops in the form of psychological empowerment through improvement of self-belief and perception (intrapersonal component), development of understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The process of accepting the disease was also identified among the interviewees as a facilitating condition for patient empowerment. Rai et al (2022) demonstrated that accepting of living with diabetes is a condition of empowerment. Data reveal that the time required varies across patients, ranging from several months to several years.…”
Section: Resultsmentioning
confidence: 99%
“…The process of accepting the disease was also identified among the interviewees as a facilitating condition for patient empowerment. Rai et al (2022) demonstrated that accepting of living with diabetes is a condition of empowerment. Data reveal that the time required varies across patients, ranging from several months to several years.…”
Section: Resultsmentioning
confidence: 99%